Determinants of Exclusive Breastfeeding Among Mothers of Infants Less Than Six Months of Age in Mogadishu: A Facility-Based Cross-Sectional Study - Abdullahi Dahie, Hassan; Abdullahi Osman, Mohamed; Ali Jimale, Yusuf; Ibrahim Mohamud, Falis; Ahmed Hussein, Hamdi; Osman Alasow, Mohamed; Abdi Osman, Abukar; Mohamed Abdullahi, Abdirahman; Maalin Dakane, Mohamed (Journal of Pediatric Health And Nutrition, 2024)
Background Breastfeeding is a vital practice for infant health and well-being, with exclusive breastfeeding (EBF) during the first six months being particularly crucial. Despite its benefits, EBF is sub-optimally practiced in many low-to-middle income countries. This study focuses on Somalia, a country with historical political instability and poor health indicators, aiming to identify the prevalence and determinants of exclusive breastfeeding among women with infants under six months attending SOS Mother and Child Hospital in Mogadishu. Methods A hospital-based cross-sectional design was used, and data were collected through a structured questionnaire. The study sample consisted of 345 mothers, selected using a systematic sampling technique. Descriptive, bivariate, and multivariate analyses were conducted to assess breastfeeding practices and determine factors influencing exclusive breastfeeding prevalence. Result The study found that the prevalence of exclusive breastfeeding among the study population in Somalia was 44%, influenced by factors such as maternal education, employment, and utilization of antenatal and postnatal care services. Male infants and younger infants had higher odds of being exclusively breastfed. Conclusion and recommendations The study emphasizes the importance of promoting exclusive breastfeeding as the optimal feeding practice for infants in Somalia, highlighting the need for comprehensive health education during antenatal care visits and postnatal counseling. It recommends the development of supportive policies, such as maternity leave and workplace accommodations, along with community-based initiatives and support groups to facilitate and encourage exclusive breastfeeding practices.
Keywords: Exclusive breastfeeding; Initiation of breastfeeding; Feeding practices; Mixed feeding; Infant formula; Child health; Ante natal care (ANC); Post natal care (PNC)